COVID-19 and the governmentality of emergency food in the City of Turin. Issue 6 (10th May 2021) - Sargiacomo, Massimo; Corazza, Laura; D'Andreamatteo, Antonio; Dumay, John; Guthrie, James
Abstract : Purpose: This paper shows the accounting, accountability and calculative practices associated with emergency food allocations by the City of Turin through a program to feed the vulnerable during COVID-19. Design/methodology/approach: This is a single case study framed by Foucault's governmentality concept. The data was collected through interviews with key institutional actors and triangulated against decrees, circulars, ordinances and other publicly available documents. Findings: The accounting tools of governmentality are always incomplete. Sometimes unique situations and crises help us to revise and improve the tools we have. Other times, they demand entirely new tools. Research limitations/implications: Accounting needs both things to count and a context to count them. In the case of food assistance, what is counted is people. In Turin's case, many people had never been counted – either because there was no need or because they were unaccounted for by choice. Now, the government was accountable for the welfare of both. Thus, new classification systems emerged, as did organisational and accounting solutions. Originality/value: Although the accounting-for-disasters literature is diverse, studies too often favour the macro social, economic and political issues surrounding crises, neglecting the micro issues associated with governmentality and calculative practices.